Antibacterial Activity Test Of Extracts And Fractionsn-Hexane, Ethyl Acetate, And Pineapple Peel Water (Ananas Comosus(L.) Merr.) Against Bacteria Propionibacterium Acnes ATCC 6919 - Dian Fatimatus Salwa; Tatiana Siska Wardani; Bangkit Riska Permata (International Journal of Health Engineering and Technology, 2026)
Acne vulgaris is a common dermatological problem in adolescents in Indonesia's tropical climate related to the activity of Propionibacterium acnes bacteria. Long-term use of antibiotics risks causing resistance, so natural antibacterial alternatives are needed. This study aims to evaluate the antibacterial activity of ethanol extract and fractions of n-Hexane, ethyl acetate, and pineapple peel water against Propionibacterium acnes ATCC 6919, and to determine the most active fraction and MIC and MBC values. This study is a quantitative experimental study. The study population was the bacterial culture of P. acnes ATCC 6919, with samples in the form of pineapple peel extract and fraction. The research instruments included disc diffusion and liquid and solid dilution methods, while data analysis used the Shapiro-Wilk, Levene, and Kruskal-Wallis tests. The results showed that the ethanol extract had moderate to strong antibacterial activity, the ethyl acetate fraction showed the highest activity compared to other fractions, while the n-hexane fraction showed no activity. MIC and MBC values ​​were obtained at a concentration of 20 percent. The conclusion of this study is that pineapple peel has the potential as a natural antibacterial source against P. acnes and the ethyl acetate fraction is the most active fraction.